Архитектор Иван Чарушин - Минин Рудольф Андреевич (Удмуртия, 2020)
Экземпляры: (20201008) / Инвентарный номер: 41620 / Цена: 450.00 / Сис.шифр: 85.113(2=664.1) / Авт.знак: М 61 / ГРНТИ: 18 / ББК: 85.113(2=664.1)